Combinatorial signaling by the Frizzled/PCP and Egfr-pathways during planar cell polarity establishment in the Drosophila eye - Weber, Ursula (2008)
Frizzled (Fz)/PCP signaling regulates planar, vectorial orientation of cells or groups of cells within whole tissues. Although Fz/PCP signaling has been analyzed in several contexts, little is known about nuclear events acting downstream of Fz/PCP signaling in the R3/R4 cell fate decision in the Drosophila eye or in other contexts. Here we demonstrate a specific requirement for Egfr-signaling and the transcription factors Fos (AP-1), Yan and Pnt in PCP dependent R3/R4 specification. Loss and gain-of-function assays suggest that the transcription factors integrate input from Fz/PCP and Egfr-signaling and that the ETS factors Pnt and Yan cooperate with Fos (and Jun) in the PCP-specific R3/R4 determination. Our data indicate that Fos (either downstream of Fz/PCP signaling or parallel to it) and Yan are required in R3 to specify its fate (Fos) or inhibit R4 fate (Yan), and that Egfr-signaling is required in R4 via Pnt for its fate specification. Taken together with previous work establishing a Notch-dependent Su(H) function in R4, we conclude that Fos, Yan, Pnt, and Su(H) integrate Egfr, Fz, and Notch-signaling input in R3 or R4 to establish cell fate and ommatidial polarity.